ANALISIS PENGUASAAN HURUF POLIFONIK PADA MAHASISWA ANGKATAN 2019 PRODI PENDIDIKAN BAHASA MANDARIN FKIP UNTAN - Lina Wati; Yoanna Afrimonika; Lusi Lusi (Universitas Tanjungpura, 2022)
Polyphonic characters are the most special type of Chinese characters. It not only has multiple pronunciations, but also multiple meanings. Therefore, polyphonic characters have always been a difficult point for students to learn Chinese. Students often misread, misinterpret, and cause errors in listening, reading comprehension, and oral expression. In order to understand the mastery of polyphonic characters and the difficulties in the use of polyphonic characters by the 2019 students majoring in Chinese education at the School of Teacher Education, Tanjung Pura University, the author used test research methods, questionnaire research methods and literature research methods to conduct research. The test results show that the students' mastery of polyphonic characters is 59.69%. From the results of the study, it can be known that students do not master polyphonic characters very well. The part where students do not master polyphonic characters is in making sentences, and the correct rate is only 32.41%. The author found that the difficulty for students with polyphonic characters lies in the pronunciation and usage of polyphonic characters. This is because students rarely communicate in Chinese, read too little, and when encountering polyphonic characters, students will guess the pronunciation and meaning by themselves, so they do not understand the pronunciation and usage of polyphonic characters.